The effect of irrigation management with saline and fresh water on some soil properties and wheat crop growth (Triticum aestivum L.) - Lujain Abed Tuama , Lujain Abed Tuama; Mohamed M. Yaseen , Mohamed M. Yaseen; Yahya J. Shabeeb , Yahya J. Shabeeb (University of Thi-Qar Journal of agricultural research, 2024)
Arid and semi-arid regions suffer from a sharp decline in rainfall and scarcity of good fresh water. This forces them to use saline water for irrigation, which can affect the growth and productivity of plants in terms of quantity and quality. So, good management and specific methods are required in the use of irrigation water. A factorial experiment was conducted with three factors in a silty clay soil, including irrigation water salinity 3, 5 and 7 dS m-1 (S1, S2, and S3) respectively. Saline irrigation water level 100 and 66% of field capacity (W1 and W2) respectively. Fresh water (0.8≃1.1) 0, 50, and 100% of field capacity (F1, F2 and F3) respectively after tow rinses with saline water and its effect on wheat cultivation. Soil salinity and moisture content were estimated in the middle and end of the growing season at two depths 0-15 and 15-30 cm. The weight of 1000 grains and water productivity were calculated. The results showed an increase in soil salinity and moisture content with increasing irrigation water salinity for both depths. A decrease in soil salinity and moisture content with increasing irrigation water level and increasing fresh water level, for both depths. There was an increase in grain weight and water productivity with increasing saline irrigation water level, increasing fresh water level and decreasing irrigation water salinity. The triple interaction treatment when irrigated with water salinity 3 dSm-1, 100% saline irrigation water level and 100% fresh water level of field capacity achieved the highest grain weight and water productivity of 45.17 g and 3.85 kg m-3 water respectively.